2005
DOI: 10.1093/ps/84.10.1610
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary energy on performance and egg composition of Bovans White and Dekalb White hens during phase I

Abstract: A 4 x 2 factorial experiment with 4 dietary energy levels (2,719, 2,798, 2,877, and 2,959 kcal of ME/ kg) and 2 strains (Bovans White and Dekalb White) was conducted to determine the effect of dietary energy on reproductive performance, egg composition, and profits of 2 strains of commercial Leghorns. This experiment lasted 16 wk. Bovans White hens (n = 768) and Dekalb White hens (n = 768) in phase I (21 wk of age) were randomly assigned into 8 treatments (16 replicates of 12 birds/treatment). Bovans White had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
63
8
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 14 publications
13
63
8
3
Order By: Relevance
“…In regard to dietary energy, Grobas et al (1999b) and Pérez-Bonilla et al (2012a) observed similar egg quality (dirty, broken, shell-less, Haugh units, yolk pigmentation and yolk to albumen ratio) for hens fed diets containing 11.10 or 11.52 MJ AME n /kg, in agreement with the results reported herein. However, Zimmermann and Andrews (1987) and Wu et al (2005) observed a reduction in albumen quality and Junqueira et al (2006) a decrease in the percentage of shell-less eggs with increases in the energy concentration of the diet. Factors such as strain and age of the hens, as well as the ingredient composition of the diet, might affect the response of egg quality traits to variations in energy content of the diet.…”
Section: Egg Qualitymentioning
confidence: 94%
See 1 more Smart Citation
“…In regard to dietary energy, Grobas et al (1999b) and Pérez-Bonilla et al (2012a) observed similar egg quality (dirty, broken, shell-less, Haugh units, yolk pigmentation and yolk to albumen ratio) for hens fed diets containing 11.10 or 11.52 MJ AME n /kg, in agreement with the results reported herein. However, Zimmermann and Andrews (1987) and Wu et al (2005) observed a reduction in albumen quality and Junqueira et al (2006) a decrease in the percentage of shell-less eggs with increases in the energy concentration of the diet. Factors such as strain and age of the hens, as well as the ingredient composition of the diet, might affect the response of egg quality traits to variations in energy content of the diet.…”
Section: Egg Qualitymentioning
confidence: 94%
“…Factors such as strain and age of the hens, as well as the ingredient composition of the diet, might affect the response of egg quality traits to variations in energy content of the diet. For example, Zimmermann and Andrews (1987) and Junqueira et al (2006) used Leghorn hens in the second cycle of egg production and Wu et al (2005) reported that the decrease in AME n of the diet reduced yolk size, which in turn could affect egg size and other egg quality traits.…”
Section: Egg Qualitymentioning
confidence: 99%
“…Feed intake was significantly decreased with the higher levels of dietary energy (Wu et al, 2005a(Wu et al, , 2005b. Similarly, as the methionine + cysteine level increased from (0.61%, 0.68%, 0.75% and 0.82 to 0.89%), a linear reduction was observed in the feed intake (P<0.01) of brown-egg laying hens (Filho et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Elde edilen bulgular, tavukların yem tüketimini enerji ihtiyaçlarına dolayısıyla rasyon enerji düzeyine göre ayarlayabilmelerine bağlı olarak, rasyon enerji düzeyi arttıkça yem tüketiminin azaldığı yönün-deki çalışmaları desteklemektedir (16,17,36,37). Tavukçulukta toplam maliyetler içerisinde en önemli payı yem gideri aldığından yem tüketiminin düşük olması, üretim maliyetlerinin de büyük oranda azalmasına dolayısıyla işletme kârının artmasına yol açmaktadır.…”
Section: Bulgularunclassified